1995
DOI: 10.1177/027112149501500205
|View full text |Cite
|
Sign up to set email alerts
|

Literacy-Rich Environments and the Transition of Young Children with Special Needs

Abstract: The present article focuses on achieving four critical competencies that are essential for children's successful transitions from preschool special education programs to the primary grades: readiness to maximize academic achievement, prosocial and age-appropriate social skills, appropriate responsiveness to various instructional styles, and appropriate responsiveness to new and different environmental structures. Children may obtain these four competencies within the context of natural, literacy-rich classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…Setting literacy skills as academic goals has been noticably absent. However, recent research in emergent literacy has stimulated the addition of goals for the development of literacy skills (DeBaryshe & Buell, 1996), including goals for pre-writing skills with students who have serious disabilities (Katims, 1991;Koppenhaver et al, 1991;DeCoste, 1993;Meyers, 1994;Katims & Pierce, 1995;Hutinger, 1996;MacArthur, 1996).…”
Section: Educational Curriculummentioning
confidence: 99%
See 2 more Smart Citations
“…Setting literacy skills as academic goals has been noticably absent. However, recent research in emergent literacy has stimulated the addition of goals for the development of literacy skills (DeBaryshe & Buell, 1996), including goals for pre-writing skills with students who have serious disabilities (Katims, 1991;Koppenhaver et al, 1991;DeCoste, 1993;Meyers, 1994;Katims & Pierce, 1995;Hutinger, 1996;MacArthur, 1996).…”
Section: Educational Curriculummentioning
confidence: 99%
“…Acquiring language skills that eventually lead to the outcome of spoken language, reading and writing begins from the moment an infants' senses are stimulated by environmental sights and sounds (Anderson et al, 1985;Wolery & Ashton-Wolery, 1992;Katims & Pierce, 1995;Koppenhaver et al, 1995;Pierce, 1996;Watkins, 1996;Kuhl et al, 1997;Saint-Laurent et al, 1996Kliewer & Landis, 1999;Justice et al, 2002).…”
Section: Early Childhood/early Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rimm-Kaufman and suggested this theoretical framework is best suited and substantiated by research focused on transitions for students with identified disabilities (Fowler, Schwartz, & Atwater, 1991;Katims & Pierce, 1995;Repetto & Correa, 1996;Roberts, Akers, & Behl, 1996;Rous, Hemmeter, & Schuster, 1994). There is a focus on changing contexts and relationships over time for children with identified disabilities, transitioning from home to preschool and preschool to formal schooling.…”
Section: Critique Of the Ecological And Dynamic Model Of Transitionmentioning
confidence: 99%
“…Moni and Jobling (2001) using socio-cultural approaches to literacy teaching and learning also showed significant progress within a group of individuals with Down syndrome aged 18 to 22 years across a 2-year program. Other studies to support positive literacy outcomes for individuals with intellectual disabilities have included both anecdotal reports (Anderson, 1995;O'Neal, 1991;Westby & Coslow, 1991) and research-based findings (Katims, 1991;Katims & Pierce, 1995;Pershey & Gilbert, 2002). Generally, it would seem that research data have shown that when adults with intellectual disabilities are provided with opportunities to broaden their literacy education through appropriate teaching and learning strategies they continue to develop and improve their language and literacy skills.…”
Section: Introductionmentioning
confidence: 99%